When people rise in protest: Mobilizing for equal citizenship in India - Hasan, Zoya; Jha, Avisheck (Haryana (India) Three essays collective, 2024)
This is an important book on the nationwide protests against the CAA (Citizenship Amendment Act) and its connections with the NRC (National Register of Citizens). It highlights the significance of vast numbers of Indians rising in protest for equal citizenship and how it became a metaphor for not just minority rights but for the safeguarding of the Constitution and democracy in contemporary India.
Keywords: Citizenship India; Equality India; Indian constitution